Cu(II)-Mediated Aminooxygenation of Alkenylimines and Alkenylamidines with TEMPO - Sanjaya, Stephen; Chua, Sze Hui; Chiba, Shunsuke (Synlett, 2012)
A method for the synthesis of oxymethyl dihydropyrroles (pyrrolines) and dihydroimidazoles has been developed via Cu(II)-mediated intramolecular aminooxygenation of alkenylimines and alkenylamidines, respectively, with 2,2,6,6-tetramethyl-1-piperidinyloxy radical (TEMPO).
Keywords: copper; TEMPO; dihydropyrroles (pyrrolines); dihydroimidazoles